2019
DOI: 10.1038/s41598-019-52628-1
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling reveals exposure to predicted end-of-century ocean acidification as a stealth stressor for Atlantic cod larvae

Abstract: Ocean acidification (OA), a direct consequence of increasing atmospheric CO2 concentration dissolving in ocean waters, is impacting many fish species. Little is known about the molecular mechanisms underlying the observed physiological impacts in fish. We used RNAseq to characterize the transcriptome of 3 different larval stages of Atlantic cod (Gadus morhua) exposed to simulated OA at levels (1179 µatm CO2) representing end-of-century predictions compared to controls (503 µatm CO2), which were shown to induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…CC-BY-NC-ND 4.0 International license perpetuity. It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted September 19, 2022. ; https://doi.org/10.1101/2022.09.18.508416 doi: bioRxiv preprint response to elevated CO2 in the brain and gills of fish (Heuer & Grosell, 2014;Kang et al, 2022;Mittermayer et al, 2019;Monroe et al, 2021) suggesting that high CO2 levels affect the expression and activity of CA. Additionally, transcripts encoding potassium channel transporters, and a Na + /K + transporting ATPase were DE in the gobies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CC-BY-NC-ND 4.0 International license perpetuity. It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted September 19, 2022. ; https://doi.org/10.1101/2022.09.18.508416 doi: bioRxiv preprint response to elevated CO2 in the brain and gills of fish (Heuer & Grosell, 2014;Kang et al, 2022;Mittermayer et al, 2019;Monroe et al, 2021) suggesting that high CO2 levels affect the expression and activity of CA. Additionally, transcripts encoding potassium channel transporters, and a Na + /K + transporting ATPase were DE in the gobies.…”
Section: Discussionmentioning
confidence: 99%
“…Carbonic anhydrase (CA), an enzyme which plays a key role in CO 2 excretion, acid-base balance, and ion-regulation was upregulated in gobies from the CO 2 seep, which could facilitate increased CO 2 excretion thereby preventing acidosis and also enhance transport of O 2 to the brain (Rummer & Brauner, 2011). Various other CA isoforms have been identified to be DE in response to elevated CO 2 in the brain and gills of fish (Heuer & Grosell, 2014; Kang et al, 2022; Mittermayer et al, 2019; Monroe et al, 2021) suggesting that high CO 2 levels affect the expression and activity of CA. Additionally, transcripts encoding potassium channel transporters, and a Na + /K + transporting ATPase were DE in the gobies.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, complex responses were found. For example, Mittermayer et al (2019) found a limited cellular response to OA in larvae yet at the same stage post hatch larvae were also found to have high mortality. The authors suggested that not enough is known about the mechanism that produces a response to OA in Atlantic Cod.…”
Section: Knowledge Gap 1: Lack Of Studies On Oa Impacts On Fish and Their Supporting Food Websmentioning
confidence: 99%
“…Conversely, proxies based on the analysis of mRNA expression are very useful to investigate the physiological impact of environmental cues on small organisms since they do not require a lot of biological material. Moreover, numerous studies demonstrated that OA-induced physiological disturbances were associated with regulation of gene expression (Cline et al, 2020, Frommel et al, 2020, Hamilton et al, 2017, Huth and Place, 2016, Lai et al, 2017, Mazurais et al, 2020a, Mazurais et al, 2020b, Shrivastava et al, 2019, Preus-Olsen et al, 2014, Tseng et al, 2013, Mittermayer et al, 2019, Michael et al, 2016. In particular, changes in mRNA levels of proteins involved in neural signalling processes have been observed in olfactory systems of fish exposed to OA (Williams et al, 2019, Porteus et al, 2018, including early stages of development (Rong et al, 2018).…”
Section: Introductionmentioning
confidence: 99%